Effect of Notoginsenoside R1 on reparative dentin formation via regulating the function of human dental pulp stem cells - Xuan He; Dan Liang; Xinyi Zhao; Kaixin Liu; Zicheng Zhang; Meiling Li; Xuemeng Ma; Wenxia Chen; Xiaoyi Zhong (Tissue and Cell, 2027)

A natural special-shaped MXene/bamboo evaporator with synergistic hydrothermal management for solar water purification - Jinhong He; Zongpei Zhang; Tianqing Shu; Weisheng Yang; Xiaoxu Ma; Jingren Ma; Meiling Chen; Fengshan Zhang; Guigan Fang; Huining Xiao; Jingquan Han (Desalination, 2026)

Inner Ear Organoids: Recent Progress and Challenges - Yingxinyu Li; Cairong He; Jiayan Liu; Haiqin Zhang; Hongxia Zhang; Zheyu He; Mengyang He; Meiling Chen; Feiyan Zhou; Jie Ding (Stem Cell Reviews and Reports, 2026)

Pseudomonas aeruginosa in Chinese mitten crab Eriocheir sinensis: Identification, pathogenic potential and control with Bdellovibrio powder - Li He; Yueqi Yang; Yiyao Liu; Meiling Liu; Haipeng Cao; Chunlei Gai; Weidong Ye (Journal of Invertebrate Pathology, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Pioneer Plants Improved the Suitability of Lead–Zinc Tailings for Plant Growth - He Gong; Xusheng Jiang; Hui Qiu; Luyang Wang; Meiling Zhang; Xinyue Teng; Jie Liu (Water, Air, & Soil Pollution, 2026)

Iron single-atom/cluster nanozyme with enhanced oxidase-like activity for fluorescent/colorimetric analysis of Total antioxidant capacity in food - Meiling Chen; Yongmin Lei; Junlin Liu; Qiming Liu; Xingjian Song; Ting He; Guo-jun Zhang; Yujie Sun; Yulin Zhang; Yuqing Qin; Shaowei Chen (Food Chemistry, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Porous Eu-ox metal–organic framework enabling open-channel carrier transport and durable Pb2+ immobilization in perovskite solar cells - Zhihang Zhang; Xiaolong Cao; Tiantian Lv; Zhengyan He; Haiyan Sun; Hai Zhong; Qi Zhang; Changlin Yao; Wen Li; Shufang Zhang; Meiling Feng (Chemical Engineering Journal, 2026)

An Ultrasensitive 1,2,3-Triazole Schiff-Based Fluorescence Probe for the Detection of Al3+ and Developing Application of Biological Activity - Chunyang Liu; Junfeng Chen; Xun Kang; Meiling Le; Huajie J. Feng; Wenying Y. He (Journal of Fluorescence, 2026)

Cationic polyacrylamide (CPAM) assisted leaching of rare earth ore containing clay minerals by inhibiting swelling and promoting permeation of ammonium sulfate solution - Meiling Jiang; Huifang Yang; Wenqian Cui; Yunbo Yang; Zhenyue Zhang; Zhengyan He; Zhigao Xu; Ming Wu; Jun Zhao; Ruan Chi (Hydrometallurgy, 2026)

FeOOH@HAnB catalyst with exposed (211) facet: High stability and new degradation routes for tetracycline - Yingru Huang; Meiling Zhou; Yaping Zhang; Yufeng He; Yuanyuan Xie; Rongmin Wang (Environmental Research, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Characteristics, sources, and health risks of fine particulate matter in Wuhan subway, China - Ji-Liang Lü; Qing Han; Zhen Wang; Min Tao; Xun Hu; Meiling Cao; Qingzhu Huang; Mengdie Shi; Zhenyu He; Xiaohu Zhao (Science of The Total Environment, 2025)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Integrated effect of aspect ratio and tree spacing on pedestrian thermal comfort of street canyon - Xiaoping Chen; Meng Han; Jinyu He; Hang Ma; Meiling Han; Yanhong Liu; Xiaogang Wu (International Journal of Biometeorology, 2024)

Designing a multi-level reverse logistics network for waste batteries of electric vehicles under uncertainty—A case study in the Yangtze River Delta Urban Agglomerations of China - Meiling He; Qipeng Li; Xiaohui Wu; Kazuhiro Izui (Journal of Cleaner Production, 2024)

A novel multi-level reverse logistics network design optimization model for waste batteries considering facility technology types - Meiling He; Qipeng Li; Xiaohui Wu; Xun Han (Journal of Cleaner Production, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Synthesis of MnOOH-hydroxyapatite nanowires for degradation of tetracycline - Shenglan Zhao; Meiling Zhou; Jiarui Ren; Yaping Zhang; Yufeng He; Rongmin Wang (Journal of Environmental Chemical Engineering, 2023)

Black carp LGP2 suppresses RIG-I mediated IFN signaling during the antiviral innate immunity - Yixuan He; Ji Liu; Yujia Miao; Meiling Liu; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2023)

Progress on the roles of zinc in sperm cryopreservation - Yuanyou Li; Shaoyu Qin; Wenfei Cui; Fan Zhao; Meiling He; Zhongliang Jiang (Theriogenology, 2023)

Balancing resources and sustainability: Analyzing the impact of mineral resources utilization on green growth - Shixiong Cheng; Can Shu; Meiling Jin; Yuhang He (Resources Policy, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Development and Characterization of Multifunctional Wound Dressing with the Property of Anti-bacteria and Angiogenesis - Xi He; Meiling Zhou; Xuemei Chen; Jing Wang; Xiaoli Zhao; Yanxia Zhu; Tao Liu (Probiotics and Antimicrobial Proteins, 2023)

Efficacy and safety of IL-23 inhibitors in the treatment of psoriatic arthritis: a meta-analysis based on randomized controlled trials - Xiaojing Huang; Haojie Shentu; Yujing He; Haijia Lai; Chen Xu; Meiling Chen; Haowei Zhu (Immunologic Research, 2023)
In recent years, the use of interleukin (IL) 23 inhibitors in the treatment of psoriatic arthritis (PsA) has been the subject of much research. By specifically binding to the p19 subunit of IL-23, IL-23 inhibitors block downstream signaling pathways and inhibit inflammatory responses. The objective of this study was to assess the clinical efficacy and safety of IL-23 inhibitors in the treatment of PsA. PubMed, Web of Science, Cochrane Library, and EMBASE databases were searched from the time of conception to June 2022 for randomized controlled trials (RCTs) investigating the use of IL-23 in PsA therapy. The main outcome of interest was the American College of Rheumatology 20 (ACR20) response rate at week 24. We included six RCTs (3 studies on guselkumab, 2 on risankizumab, and 1 on tildrakizumab) with a total of 2971 PsA patients in our meta-analysis. We found that the IL-23 inhibitor group showed a significantly higher ACR20 response rate compared to the placebo group (relative risk = 1.74, 95% confidence interval: 1.57–1.92; P < 0.001; I 2 = 40%). There was no statistical difference in the risk of adverse events ( P = 0.07) and serious adverse events ( P = 0.20) between the IL-23 inhibitor and placebo groups. Notably, the rate of elevated transaminases in the IL-23 inhibitor group was higher than the placebo group (relative risk = 1.69; 95%CI 1.29–2.23; P < 0.001; I 2 = 24%). In the treatment of PsA, IL-23 inhibitors significantly outperform placebo intervention while maintaining a favorable safety profile.

Evaluation of the outdoor thermal environment for three typical urban forms in Nanjing, China - Ji-Yu Deng; Yueyang He; Meiling Dai (Building and Environment, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Intermetallic niobium boride toward efficient adsorption and catalysis of polysulfides in Lithium-Sulfur batteries - Li He; Yingjie Cheng; Qiuju Li; Hainan Zhao; Meiling Wang; Xuejian Shi; Xiaoxin Zou; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

Correction to: Construction of HAnW‑based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Construction of HAnW-based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

The Role of Arachidonic Acid Metabolism in Myocardial Ischemia–Reperfusion Injury - Changjiang Zhang; Meiling He; Lihua Ni; Ke He; Ke Su; Yinzhi Deng; Yuanhong Li; Hao Xia (Cell Biochemistry and Biophysics, 2020)

Important interaction of chemicals, microbial biomass and dissolved substrates in the diel hysteresis loop of soil heterotrophic respiration - Qing Wang; Nianpeng He; Yuan Liu; Meiling Li; Li Xu; Xuhui Zhou (Plant and Soil, 2018)

Latitudinal patterns and influencing factors of soil humic carbon fractions from tropical to temperate forests - Li Xu; Chunyan Wang; Jianxing Zhu; Yang Gao; Meiling Li; Yuliang Lv; Guirui Yu; Nianpeng He (Journal of Geographical Sciences, 2018)

Molecular cloning and expression analysis of major intrinsic protein gene in Chlamydomonas sp. ICE-L from Antarctica - Lulu Li; Meiling An; Changfeng Qu; Zhou Zheng; Yibin Wang; Fangming Liu; Yingying He; Xiaodong He; Jinlai Miao (Extremophiles, 2017)

Cloning and structure of a histocompatibility class IIA gene (Lelo-DAA) in Chinese longsnout catfish (Leiocassis longirostris) - Tong Shen; Xiaoshun He; Meiling Lei; Jingru Wang; Xiuming Li; Jianming Li (Genes & Genomics, 2014)

Steroid 5-alpha-reductase type 2 (SRD5A2) V89L and A49T polymorphisms and sporadic prostate cancer risk: a meta-analysis - Qiaoxin Li; Yao Zhu; Jing He; Mengyun Wang; Meiling Zhu; Tingyan Shi; Lixin Qiu; Dingwei Ye; Qingyi Wei (Molecular Biology Reports, 2013)

Phylogenetic relationships and estimation of divergence times among Sisoridae catfishes - MeiLing Yu; ShunPing He (Science China Life Sciences, 2012)